Influence of processing route on the alloying behavior, microstructural evolution and thermal stability of CrMoNbTiW refractory high-entropy alloy. Issue 12 (29th June 2020) - Raman, Lavanya; Karthick, G.; Guruvidyathri, K.; Fabijanic, Daniel; Narayana Murty, S. V. S.; Murty, B. S.; Kottada, Ravi S.
Abstract: Abstract : Two different processing routes of mechanical alloying followed by the spark plasma sintering (powder metallurgy) and vacuum arc melting (casting route) were employed to understand the role of processing routes on the phase and microstructural evolution in an equiatomic CrMoNbTiW refractory high-entropy alloy. Besides a major BCC solid solution, a small fraction of carbide, σ phase, nitride, and oxide phases were observed in the alloys prepared by the powder metallurgy route in contrast to a single-phase BCC solid solution in the casting route. The milling atmosphere (dry milling in air and Ar) has significantly influenced the phase and microstructural evolution, illustrating the substantial role of contaminants. Good thermal stability of microstructure at high homologous temperatures was shown based on the long-term heat treatment at 1300 °C for 240 h. The phase evolution predictions via Calphad studies were found to be in reasonable agreement with the experimental observations, albeit with some limitations.